Allelic Imbalance Analysis in Liquid Biopsy to Monitor Locally Advanced Esophageal Cancer Patients During Treatment - Boldrin, Elisa; Curtarello, Matteo; Fassan, Matteo; Rugge, Massimo; Realdon, Stefano; Alfieri, Rita; Amadori, Alberto; Saggioro, Daniela (Frontiers in Oncology, 2020)
Esophageal cancer (EC) is a highly aggressive tumor and the current monitoring procedures are partially inadequate to evaluate treatment efficacy. The aim of this study was to investigate whether allelic imbalance analysis in liquid biopsy could be used as an additional tool to monitor tumor burden in EC patients. For this purpose, circulating cell free DNA (cfDNA) from 52 patients with a locally advanced EC, which underwent neoadjuvant treatment and resection, were analyzed. Data from four representative longitudinally followed patients are also reported. Furthermore, 17 DNAs from formalin fixed paraffin embedded (FFPE)-tumor samples were analyzed and compared to time-matched cfDNAs. To look for allelic imbalance, which is the main genetic alteration in both EC histotypes, we used a panel of 5 microsatellites (MSs) and 3 single nucleotide polymorphisms (SNPs) nearby to genes described as frequently altered. Fisher exact test and Mann-Whitney U test were used to analyze categorical and continuous data, respectively. The correlation coefficient between cfDNA and FFPE-DNA was calculated with the Pearson’s correlation test. We found that the selected tumor-related alterations are present in cfDNA of both adenocarcinoma (EADC) and squamous cell carcinoma (ESCC) with similar frequencies. The only exception were the MSs, one downstream and one upstream of SMAD4 whose loss was only observed in EADC (26% vs 0%, P=0.018). More interestingly, longitudinal studies disclosed that in patients with disease progression, tumor-related alterations were present in cfDNA before overt clinical or instrumental signs of relapse. In conclusion our data indicate that the evaluation of tumor-related genes allelic imbalance in cfDNA might be a useful tool to complement the current monitoring procedures for EC patients and to guide their management.